Forces during front crawl swimming at different stroke rates - Cohen, R. C. Z.; Cleary, P. W.; Mason, B. R.; Pease, D. L. (Sports Engineering, 2017)
Understanding the relationships between front crawl swimming technique and the corresponding fluid dynamics is important to athletes seeking improved performance and an edge over their rivals. Computational fluid dynamics (CFD) swimming modelling provides a controlled and unobtrusive capability that provides many previously immeasurable quantities including full flow fields and information on the forces experienced by the body throughout the stroke. In this study, a coupled biomechanical-smoothed particle hydrodynamics (SPH) method is used to determine when peak arm thrust occurs and how the ratio of arm-leg thrust changes with stroke rate. A dynamic biomechanical model of a female national-level swimmer was generated from a three-dimensional laser body scan of the athlete and multi-angle videos of sub-maximal swimming trials. This was coupled to the SPH method to simulate the fluid moving around the body during front crawl swimming. Two distinct peaks in net streamwise thrust were found during the stroke coinciding with the underwater arm strokes. The peak arm thrust occurred during the transition from pull to push (left arm) and midway during the push (right arm). Finally, the ratio of arm thrust to leg thrust was found to increase with increasing stroke rate.